Becoming Eve : my journey from ultra-Orthodox rabbi to transgender woman - Stein, Abby, 1991- (Seal Press, 2019)
"Abby Stein was raised in a Hasidic Jewish community in Brooklyn, profoundly isolated in a culture that lives according to the laws and practices of an eighteenth-century Eastern European enclave, speaking only Yiddish and Hebrew and shunning modern life. Stein was born as the first son in a rabbinical dynastic family, poised to become a leader of the next generation of Hasidic Jews. But Stein felt certain at a young age that she was a girl. Without access to TV or the internet, and never taught English, she suppressed her desire for a new body while looking for answers wherever she could find them, from forbidden religious texts to smuggled secular examinations of faith. Finally, she orchestrated a personal exodus from ultra-Orthodox manhood into mainstream femininity--a radical choice that forced her to leave her home, her family, and her way of life"--